2023
DOI: 10.3390/ijms241310807
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Benzothiazole and Benzoxazole Derivatives in the Discovery of Agricultural Chemicals

Abstract: Benzoxazole and benzothiazole have a broad spectrum of agricultural biological activities, such as antibacterial, antiviral, and herbicidal activities, which are important fused heterocyclic scaffold structures in agrochemical discovery. In recent years, great progress has been made in the research of benzoxazoles and benzothiazoles, especially in the development of herbicides and insecticides. With the widespread use of benzoxazoles and benzothiazoles, there may be more new products containing benzoxazoles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…Due to their substantial applications across industries, including biological, agricultural, medicinal and pharmacological fields, chemists have drawn their attention to various heterocyclic scaffolds, such as piperazines (Halimehjani et al, 2022), benzoxazole, benzothiazole (Zou et al, 2023), heterocyclic sulfonamides (Apiraksattayakul et al, 2022), benzofurans (Farhat et al, 2022), benzimidazoles (Nardi et al, 2023), thiadiazoles (Janowska et al, 2020), pyarzoles (Nazeer et al, 2023), lamivudines (Henriquez-Camacho et al, 2023), ciprofloxacin-based acetanilides (Zhang et al, 2018), triazoles (Irfan et al, 2024), quinoxalines (Montana et al, 2019), and oxadiazoles (Kerru et al, 2020;Irfan et al, 2022;Irfan et al, 2023). Notably, theophylline (Shahzadi et al, 2020;Shahzadi et al, 2022a), a naturally occurring methylxanthine, has found frequent therapeutic use in treating conditions such as asthma, respiratory deficits in premature infants, and chronic pulmonary obstructive disease (COPD).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their substantial applications across industries, including biological, agricultural, medicinal and pharmacological fields, chemists have drawn their attention to various heterocyclic scaffolds, such as piperazines (Halimehjani et al, 2022), benzoxazole, benzothiazole (Zou et al, 2023), heterocyclic sulfonamides (Apiraksattayakul et al, 2022), benzofurans (Farhat et al, 2022), benzimidazoles (Nardi et al, 2023), thiadiazoles (Janowska et al, 2020), pyarzoles (Nazeer et al, 2023), lamivudines (Henriquez-Camacho et al, 2023), ciprofloxacin-based acetanilides (Zhang et al, 2018), triazoles (Irfan et al, 2024), quinoxalines (Montana et al, 2019), and oxadiazoles (Kerru et al, 2020;Irfan et al, 2022;Irfan et al, 2023). Notably, theophylline (Shahzadi et al, 2020;Shahzadi et al, 2022a), a naturally occurring methylxanthine, has found frequent therapeutic use in treating conditions such as asthma, respiratory deficits in premature infants, and chronic pulmonary obstructive disease (COPD).…”
Section: Introductionmentioning
confidence: 99%